Inorganic oxide powder, its manufacturing method, and resin composition
By combining spherical titanium oxide powder with aluminum oxide powder and adjusting the aluminum content within a specific range, the inorganic oxide powder achieves a high dielectric constant and low dielectric loss tangent, addressing the challenges faced by existing ceramic fillers in high-frequency applications.
Patent Information
- Application Number
- JP2023523430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-24
- Filing Date
- 2022-05-18
- Publication Date
- 2025-05-01
- Estimated Expiration
- 2042-05-18
AI Technical Summary
Existing ceramic fillers used in antenna materials for high-frequency applications struggle to simultaneously achieve a high dielectric constant and a low dielectric loss tangent, often due to issues with particle size, shape, and moisture content.
An inorganic oxide powder is developed by combining spherical titanium oxide powder with aluminum oxide powder, with the amount of aluminum set within a specific range (20 to 50,000 ppm by mass), to achieve a high dielectric constant and low dielectric loss tangent when blended with a resin material.
The resulting inorganic oxide powder effectively enhances the dielectric properties of resin compositions, allowing for improved miniaturization of electronic devices while maintaining stable dielectric performance.
Smart Images

Figure 0007671345000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an inorganic oxide powder, a method for producing the same, and a resin composition containing the inorganic oxide powder. [Background technology]
[0002] In recent years, with the increase in the amount of information communication in the field of communication, the use of high-frequency band signals has become widespread in electronic devices and communication devices. On the other hand, the application of high-frequency band signals to the devices has also caused a problem of increased transmission loss of circuit signals. Therefore, materials used in high-frequency band devices are required to have low dielectric loss tangents. Furthermore, with the high functionality of related electronic materials and components, further miniaturization of devices is also required. Communication devices can be further miniaturized when the relative dielectric constant of the antenna material incorporated therein is high. Therefore, ceramic fillers (inorganic oxide fillers) used in antenna materials and the like are also required to have high dielectric constants and low dielectric loss tangents (for example, Patent Document 1, etc.). The dielectric properties of ceramic materials in the GHz band are described in, for example, Non-Patent Document 1, etc., but all of them are properties of sintered substrates.
[0003] Titanium oxide powder is known as a ceramic filler with a relatively high dielectric constant and high versatility. Titanium oxide powder is generally synthesized by a gas phase method (e.g., Patent Document 2) or a wet method (e.g., Patent Document 3). In the gas phase method, titanium oxide powder with a small average particle size is obtained, and the specific surface area is likely to be large. However, if the specific surface area is large, there is a concern that the dielectric tangent may be deteriorated due to hydroxyl groups and adsorbed water on the filler surface. In addition, in the case of the wet method, the moisture content of the titanium oxide powder obtained is likely to be high, and the dielectric tangent is also likely to be deteriorated.
[0004] Since ceramic fillers are often used by filling them into resin materials, it is desirable for the shape of the filler to be as spherical as possible in order to improve dispersibility in the resin material and stabilize the dielectric properties. Flame fusion and thermal plasma methods are known as synthesis methods that make it easy to adjust the specific surface area and obtain spherical titanium oxide powder (e.g., Patent Documents 4 and 5). However, the spherical titanium oxide powder obtained by these methods has the problem of unstable dielectric properties.
[0005] [Patent Document 1] Patent Publication No. 2021-27386 [Patent Document 2] Japanese Patent Application Publication No. 6-340423 [Patent Document 3] JP 2005-53707 A [Patent Document 4] Patent No. 4155750 [Patent Document 5] JP 2012-246203 A [Non-Patent Document 1] International Materials Reviews vol.60 No.70 Supplementary data (2015) Summary of the Invention
[0006] Therefore, an object of the present invention is to provide an inorganic oxide powder that can simultaneously achieve a high dielectric constant and a low dielectric tangent when filled into a resin material, a method for producing the same, and a resin composition containing the inorganic oxide powder.
[0007] As a result of extensive research, the inventors surprisingly discovered that by combining spherical titanium oxide powder with aluminum oxide powder and setting the amount of aluminum in the inorganic oxide powder within a certain range, it is possible to obtain an inorganic oxide powder that can simultaneously achieve a high dielectric constant and a low dielectric tangent when blended with a resin material, and thus completed the present invention. That is, the present invention has the following aspects. [1] An inorganic oxide powder comprising a spherical titanium oxide powder and an aluminum oxide powder, wherein the amount of aluminum in the inorganic oxide powder is 20 to 50,000 ppm by mass. [2] The inorganic oxide powder according to [1], wherein the inorganic oxide powder has an average circularity of 0.80 or more. [3] The inorganic oxide powder according to [1] or [2], wherein the inorganic oxide powder has an average particle size of 0.5 to 40 μm. [4] The specific surface area of the inorganic oxide powder is 5 m 2 / g or less. [5] The inorganic oxide powder according to any one of [1] to [4], wherein the proportion of the spherical titanium oxide powder is 90 mass% or more relative to the total mass of the inorganic oxide powder. [6] The inorganic oxide powder according to any one of [1] to [5], wherein the inorganic oxide powder is surface-treated with a surface treatment agent. [7] The inorganic oxide powder according to any one of [1] to [6], which is for use in filling resin materials. [8] A resin composition comprising the inorganic oxide powder according to any one of [1] to [7] and at least one resin material selected from a thermoplastic resin and a thermosetting resin. [9] A method for producing an inorganic oxide powder according to any one of [1] to [7], comprising: spheroidizing titanium oxide powder by a powder melting method; adding an aluminum source to the spheroidized titanium oxide powder; and heat-treating a raw material powder containing the aluminum source and the spherical titanium oxide powder.
[0008] According to the present invention, it is possible to provide an inorganic oxide powder that can simultaneously achieve a high dielectric constant and a low dielectric tangent when filled into a resin material, a method for producing the same, and a resin composition containing the inorganic oxide powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, one embodiment of the present invention will be described in detail, but the present invention is not limited to the following embodiment. In this specification, the description of "to" means "not less than or equal to." For example, "3 to 15" means 3 or more and 15 or less.
[0010] [Inorganic oxide powder] The inorganic oxide powder according to the present embodiment is an inorganic oxide powder containing a spherical titanium oxide powder and an aluminum oxide powder, and is characterized in that the amount of aluminum in the inorganic oxide powder is 20 to 50,000 mass ppm. When the inorganic oxide powder according to the present embodiment is filled into a resin material constituting a substrate, it can simultaneously achieve a high dielectric constant and a low dielectric tangent.
[0011] The amount of aluminum in the inorganic oxide powder according to this embodiment is 20 to 50,000 ppm by mass, preferably 20 to 40,000 ppm by mass, more preferably 40 to 40,000 ppm by mass, and even more preferably 400 to 40,000 ppm by mass. If the amount of aluminum in the inorganic oxide powder is 20 ppm by mass or more, the effect of reducing the dielectric tangent is high. Also, if the amount of aluminum in the inorganic oxide powder is 50,000 ppm by mass or less, a high dielectric constant can be achieved. In this specification, the amount of aluminum in the inorganic oxide powder can be measured under the following conditions in accordance with JIS R9301-3-4 and JIS 0116. <Method for measuring the amount of aluminum in inorganic oxide powder> 0.1 g of inorganic oxide powder is placed in a Teflon (registered trademark) container, 2 mL of 6 M sulfuric acid is added, and the Teflon container is sealed and heated in a dryer adjusted to 230°C for 16 hours. After cooling, the decomposition liquid is adjusted to 10 mL with pure water to obtain a test liquid. The test liquid is diluted with dilute sulfuric acid as necessary. The measurement sample is then analyzed by ICP emission spectrometry (ICP spectrometer: for example, Agilent, product name: 5110 VDV) to measure the amount of aluminum in the inorganic oxide powder. The measurement wavelength is 396.152 nm. The calibration curve is created using the following standard solutions. Prepare a titanium solution by dissolving 6.0 g of titanium (purity 99.9% or higher) in 50 mL of 6 M hydrochloric acid by heating and dissolving, then adjusting the volume to 100 mL. Distribute aluminum standard solution (Al1000, Fujifilm Wako Pure Chemical Industries, Ltd.) into 10 mL spinach tubes to 0 mg / L, 0.1 mg / L, 1.0 mg / L, and 10 mg / L, and add 2 mL of 6 M sulfuric acid and 1 mL of titanium solution to adjust the volume to the standard solution for the calibration curve.
[0012] The inorganic oxide powder according to the present embodiment includes a spherical titanium oxide powder and an aluminum oxide powder. The ratio of the spherical titanium oxide powder in the inorganic oxide powder is preferably 90% by mass or more, more preferably 90 to 99.998% by mass, and even more preferably 95 to 99.998% by mass, based on the total mass of the inorganic oxide powder. If the ratio of the spherical titanium oxide powder is 90% by mass or more, it is easy to simultaneously achieve a high dielectric constant and a low dielectric loss tangent when filled into a resin material. Note that the "spherical titanium oxide powder" refers to a titanium oxide powder whose projection view has a shape close to a sphere when observed under a microscope or the like. The average circularity of the spherical titanium oxide powder is preferably 0.80 or more, and more preferably 0.90 or more. The average circularity of the spherical titanium oxide powder can be calculated in the same manner as that of the inorganic oxide powder, which will be described later.
[0013] The ratio of the aluminum oxide powder in the inorganic oxide powder can be adjusted as desired within a range in which the amount of aluminum in the inorganic oxide powder is 20 to 50,000 ppm by mass. In one embodiment, the ratio of the aluminum oxide powder in the inorganic oxide powder may be 10% by mass or less, or 5% by mass or less, based on the total mass of the inorganic oxide powder. In this specification, the term "aluminum oxide" refers to a composition in which aluminum is oxidized and contains mainly aluminum and oxygen, and the composition ratio may be arbitrary, and refers to a composition containing aluminum oxide (alumina). The aluminum oxide may be single crystal, polycrystalline, or amorphous, or may be a mixture thereof.
[0014] The average circularity of the inorganic oxide powder according to this embodiment is preferably 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more. When the inorganic oxide powder has an average circularity of 0.80 or more, the inorganic oxide powder is easily dispersed in a resin material when mixed with the resin material, and the dielectric properties are easily stabilized. In addition, it is easy to prevent the resin viscosity from increasing and the flowability from decreasing, and the processability and filling properties are not easily deteriorated. Furthermore, it is easy to prevent the specific surface area from becoming too large and the dielectric properties from decreasing. Note that "stable dielectric properties" refers to a small variation in the dielectric constant and dielectric tangent values of the resin composition depending on the measurement point. In addition, "average circularity" refers to a value calculated by the following method. (Average circularity) The inorganic oxide powder is fixed with carbon tape and then coated with osmium. The powder is then photographed at a magnification of 500 to 50,000 times using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-7001F SHL), and the projected area (S) and projected perimeter (L) of the particles constituting the powder are calculated using an image analyzer (for example, manufactured by Nippon Roper Co., Ltd., product name: Image-Pro Premier Ver.9.3), and the circularity of the particles is then calculated using the following formula (1). The circularity of any 200 particles is calculated, and the average value is taken as the average circularity of the inorganic oxide powder. Circularity = 4πS / L 2 (1)
[0015] The specific surface area of inorganic oxide powder is 5m 2 / g or less is preferable, and 4m 2 / g or less is more preferable, and 3m 2 / g or less is more preferable. 2 From the viewpoint of filling the resin material, the lower limit of the specific surface area of the inorganic oxide powder is 0.1 m 2 That is, the specific surface area of the inorganic oxide powder according to this embodiment is preferably 0.1 to 5 m 2 The specific surface area of the inorganic oxide powder refers to a value measured by a fully automatic specific surface area diameter measuring device according to a BET single point method.
[0016] The average particle size of the inorganic oxide powder is preferably 0.5 to 40 μm, more preferably 1 to 30 μm, and even more preferably 1 to 20 μm. If the average particle size of the inorganic oxide powder is within the above range, the fillability into the resin material is more improved, and the dielectric constant and dielectric tangent of the resin composition are easily adjusted. The average particle size of the inorganic oxide powder refers to the particle size at which the cumulative value corresponds to 50% in the cumulative particle size distribution on a volume basis measured using a laser diffraction particle size distribution measuring device. The cumulative particle size distribution is represented by a distribution curve with the particle size (μm) on the horizontal axis and the cumulative value (%) on the vertical axis.
[0017] The spherical titanium oxide powder contained in the inorganic oxide powder according to this embodiment preferably has a rutile phase as a crystal phase. By including spherical titanium oxide powder having a rutile phase, the inorganic oxide powder obtained is more likely to achieve a higher dielectric constant. When spherical titanium oxide powder having a rutile phase is included, the ratio of the spherical titanium oxide powder having a rutile phase in the inorganic oxide powder according to this embodiment may be 90% by mass or more, 95% by mass or more, or 98% by mass or more. Note that "the ratio of the spherical titanium oxide powder having a rutile phase in the inorganic oxide powder" means the ratio of the spherical titanium oxide powder having a rutile phase to the total crystal phase (including the amorphous phase) contained in the inorganic oxide powder. The identification of the crystal phase in the inorganic oxide powder and the ratio of each crystal phase can be determined by powder X-ray diffraction measurement / Rietveld analysis.
[0018] The inorganic oxide powder according to the present embodiment may be surface-treated with a surface treatment agent. Examples of the surface treatment agent include a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and the like. These may be used alone or in combination of two or more. By being surface-treated, the filling property into the resin material tends to be improved. When the surface is treated with a surface treatment agent, the entire surface of the inorganic oxide powder may be modified, or only a part of the surface may be modified.
[0019] The inorganic oxide powder according to the present embodiment may contain other inorganic oxide powders other than spherical titanium oxide powder and aluminum oxide powder. Examples of other inorganic oxide powders include silica powder, magnesium oxide powder, zirconium oxide powder, strontium titanate powder, barium titanate powder, etc. The ratio of other inorganic oxide powders is preferably 5 mass% or less with respect to the total mass of the inorganic oxide powder according to the present embodiment. In addition, since it is easy to obtain an inorganic oxide powder that can simultaneously achieve a high dielectric constant and a low dielectric tangent, it is preferable that the inorganic oxide powder according to the present embodiment is substantially composed of only spherical titanium oxide powder and aluminum oxide powder. That is, the ratio of other inorganic oxide powders in the inorganic oxide powder according to the present embodiment is preferably less than 0.1 mass%. Furthermore, the inorganic oxide powder according to this embodiment may be a mixture of inorganic oxide powders having different specific surface areas, average particle sizes, and the like.
[0020] [Method of manufacturing inorganic oxide powder] Next, a method for producing an inorganic oxide powder according to this embodiment will be described. The inorganic oxide powder according to the present embodiment includes a step of spheroidizing titanium oxide powder by a powder melting method (step (i)), adding an aluminum source to the spheroidized titanium oxide powder (step (ii)), and heat-treating a raw material powder containing the aluminum source and the spherical titanium oxide powder (step (iii)). By using this production method, an inorganic oxide powder can be obtained that contains spherical titanium oxide powder and aluminum oxide powder and has an aluminum content of 20 to 50,000 ppm by mass.
[0021] <Process (i)> The method for producing an inorganic oxide powder according to this embodiment includes spheroidizing titanium oxide powder by a powder melting method (hereinafter, referred to as the "spheroidizing step"). As the raw material titanium oxide powder (hereinafter simply referred to as "titanium oxide powder"), it is preferable to use titanium oxide powder having an average particle size of 0.5 to 40 μm. In addition, the average circularity of the titanium oxide powder is not particularly limited. With such titanium oxide powder, the moisture content can be more easily reduced in the subsequent step of heat-treating the raw material powder (powder containing spherical titanium oxide powder and an aluminum source). Therefore, as the titanium oxide powder, as long as it has the above-mentioned average particle size, one obtained by a wet method or one obtained by granulating fine titanium oxide powder may be used as the raw material. The average particle size of the titanium oxide powder can be calculated in the same manner as the inorganic oxide powder described above.
[0022] Titanium oxide powder is free of impurities of alkali metals such as Li, Na, and K, metal elements such as Fe, and Cl, from the viewpoint of reducing the dielectric tangent and the reliability of electronic materials. - , Br - It is preferable that the content of anions such as these is small. Specifically, it is preferable that the total content of these impurities and anions in the raw material titanium oxide powder is 0.01 mass % or less. The titanium oxide powder may contain aluminum. When using titanium oxide powder containing aluminum, it is preferable to adjust the amount of aluminum source added in the next step (ii) so that the amount of aluminum in the inorganic oxide powder is 20 to 50,000 mass ppm. That is, the amount of aluminum in the inorganic oxide powder according to this embodiment may be the total amount of aluminum derived from the raw titanium oxide powder and the amount of aluminum derived from the aluminum source added in the step (ii) described below.
[0023] Step (i) is a step of spheroidizing titanium oxide powder by a powder melting method. The powder melting method is a method of spheroidizing titanium oxide powder by introducing it into a high-temperature condition above the melting point, such as a flame, plasma, electric furnace, or gas furnace, and can be, for example, the methods described in Patent Documents 4 and 5. The melting atmosphere is not particularly limited, but from the viewpoint of easily preventing reduction of titanium oxide powder, it is desirable to spheroidize it in an environment with a high oxygen partial pressure, and for example, it can be spheroidized in a flame using LPG / O2 gas.
[0024] The average circularity of the titanium oxide powder after the spheroidizing step (spherical titanium oxide powder) is preferably 0.80 or more, and more preferably 0.90 or more. The average particle size of the spherical titanium oxide powder may be 0.5 to 40 μm, or may be 1 to 30 μm.
[0025] <Process (ii)> Next, an aluminum source is added to the spherical titanium oxide powder. The step of adding the aluminum source may be a step of unavoidably mixing aluminum during production, or a step of adding an aluminum compound. Here, "aluminum inevitably mixed" refers to the aluminum source contained in the raw titanium oxide powder. When the titanium oxide powder contains aluminum, it is preferable to adjust the amount of aluminum source added so that the amount of aluminum in the finally obtained inorganic oxide powder is 20 to 50,000 ppm by mass.
[0026] When an aluminum compound is added as an aluminum source, for example, alumina, aluminum hydroxide, boehmite, aluminum acetate, aluminum nitrate, acetoalkoxyaluminum diisopropylate, metallic aluminum, etc. can be used. These may be used alone or in combination of two or more. Among these, it is preferable to use alumina, aluminum hydroxide, and boehmite from the viewpoint of reducing the amount of impurities. From the viewpoint of uniformity of reaction, the specific surface area (BET) of the aluminum compound is set to 5 m 2In one embodiment, the aluminum compound has a specific surface area of 5 to 120 m 2 It is more preferable to use an alumina fine powder having a particle size of 1 / g. The aluminum source can be added in the form of a powder that dissolves in a solvent such as water or alcohol, for example, Al(CH3COO)3 (aluminum acetate). 、 When an aluminum compound such as acetoalkoxyaluminum diisopropylate is used, it may be added in a state dissolved in a solvent such as water or alcohol, but from the viewpoints of mass productivity and cost, it is preferable to add it in a powder state.
[0027] It is preferable to add an aluminum compound so that the amount of aluminum in the inorganic oxide powder is 20 to 50,000 ppm by mass, and then uniformly mix the spherical titanium oxide powder and the aluminum compound using a ball mill, various mixers, etc. From the viewpoints of mass productivity and cost, it is preferable to mix them in a dry manner.
[0028] <Step (iii)> Next, the raw material powder containing the aluminum source and the spherical titanium oxide powder is heat-treated. The heating temperature is preferably 700 to 1300°C, more preferably 800 to 1100°C. By heat-treating the raw material powder at such a heating temperature, it becomes easier to obtain an inorganic oxide powder that can simultaneously achieve a high dielectric constant and a low dielectric tangent. In addition, it becomes easier to obtain an inorganic oxide powder that has excellent dispersibility in a resin material. The heating device may be the same as that used in the above-mentioned step (i). Step (iii) is preferably performed in the atmosphere. The heating time is preferably 1 to 24 hours, more preferably 1 to 12 hours. If the heating time is 1 to 24 hours, the productivity is likely to be good and the dielectric properties are likely to be stable.
[0029] The inorganic oxide powder according to the present embodiment can be obtained by the above-mentioned steps (i) to (iii). After step (iii), the inorganic oxide powder obtained may be in the form of aggregates. Therefore, a crushing process may be performed as necessary. The crushing method is not particularly limited, and for example, a method of crushing using an agate mortar, a ball mill, a vibration mill, a jet mill, a wet jet mill, etc. may be adopted. Crushing may be performed in a dry manner, or in a wet manner by mixing with a liquid such as water or alcohol. In the wet crushing, inorganic oxide powder can be obtained by drying after crushing. In addition, the drying method is not particularly limited, and examples thereof include heat drying, vacuum drying, freeze drying, and supercritical carbon dioxide drying.
[0030] The method for producing an inorganic oxide powder according to the present embodiment may further include a step of classifying the inorganic oxide powder in order to obtain an inorganic oxide powder having a desired average particle size. Examples of the classification method include classification using a sieve, liquid cyclone, and air classification. Furthermore, the method may include a step of surface-treating the inorganic oxide powder with a surface treatment agent, a washing step for reducing impurities (such as the above-mentioned anions) in the inorganic oxide powder, and the like.
[0031] The inorganic oxide powder according to the present embodiment may be blended or mixed with other powders having different specific surface areas or average particle sizes, or with other metal powders having the same composition or different crystal phases, to obtain a mixed powder of inorganic oxide powders. By blending the mixed powder, the dielectric constant, dielectric loss tangent, thermal expansion coefficient, thermal conductivity, packing rate, etc., when blended with a resin material, can be more easily adjusted. The "powder" may be various powders such as metal powder, ceramic powder, and resin powder, and may be mixed with various powders such as amorphous silica powder, crystalline silica powder, alumina powder, titanium oxide powder, barium titanate powder, strontium titanate powder, carbon black powder, aluminum powder, silicon powder, polyethylene powder, and PTFE powder.
[0032] As described above, the inorganic oxide powder according to the present embodiment can simultaneously achieve a high dielectric constant and a low dielectric tangent when filled into a resin material constituting a substrate or the like. +4 ) is easily reduced, and Ti 3+ This tends to cause defects in the crystals. However, it is believed that the reduction can be suppressed by adding an aluminum source and adjusting the amount of aluminum to fall within a certain range, making it easier to achieve a high dielectric constant and a low dielectric tangent.
[0033] [Application] The inorganic oxide powder according to the present embodiment can achieve a high dielectric constant and a low dielectric tangent when filled in a resin material, and can therefore be suitably used as a filler for resin materials.
[0034] [Resin composition] The resin composition according to this embodiment contains the above-mentioned inorganic oxide powder and at least one resin material selected from a thermoplastic resin and a thermosetting resin. The content of the inorganic oxide powder in the resin composition is not particularly limited and can be appropriately adjusted depending on the purpose. For example, when used as a high-frequency substrate material or an insulating material, the content of the inorganic oxide powder may be in the range of 5 to 80 mass % relative to the total mass of the resin composition, and more preferably in the range of 5 to 70 mass %.
[0035] <Resin materials> The resin composition according to the present embodiment includes at least one resin material selected from thermoplastic resins and thermosetting resins. More specifically, for example, polyethylene resin; polypropylene resin; epoxy resin; silicone resin; phenolic resin; melamine resin; urea resin; unsaturated polyester resin; fluororesin; polyamide resin such as polyimide resin, polyamideimide resin, polyetherimide resin; polyester resin such as polybutylene terephthalate resin, polyethylene terephthalate resin; polyphenylene sulfide resin; wholly aromatic polyester resin; polysulfone resin; liquid crystal polymer resin; polyethersulfone resin; polycarbonate resin; maleimide modified resin; ABS resin; AAS (acrylonitrile-acrylic rubber-styrene) resin; AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc. may be used alone or in combination of two or more.
[0036] When the resin composition according to the present embodiment is used as a substrate material for high frequency bands or an insulating material, a known low dielectric resin material used for this purpose can be used. Specifically, as the low dielectric resin material, at least one resin material selected from a hydrocarbon-based elastomer resin, a polyphenylene ether resin, and an aromatic polyene-based resin can be used. Among these, a hydrocarbon-based elastomer resin or a polyphenylene ether resin is preferred. The proportion of these resin materials is preferably 20 to 95% by mass, more preferably 30 to 95% by mass, based on the total mass of the resin composition.
[0037] The ratio of the resin material to the inorganic oxide powder in the resin composition can be appropriately adjusted according to the desired dielectric properties such as the dielectric constant and dielectric loss tangent, etc. For example, the amount of the resin material can be adjusted in the range of 10 to 10,000 parts by mass per 100 parts by mass of the inorganic oxide powder.
[0038] The resin composition according to this embodiment may contain a curing agent, a curing accelerator, a release agent, a coupling agent, a colorant, a flame retardant, an ion scavenger, etc., within a range that does not impair the effects of this embodiment.
[0039] <Method of producing resin composition> The method for producing the resin composition is not particularly limited, and the resin composition can be produced by stirring, dissolving, mixing, and dispersing a predetermined amount of each material. The apparatus for mixing, stirring, dispersing, etc. of the mixture is not particularly limited, but a mortar and pestle machine equipped with a stirring and heating device, a three-roll mill, a ball mill, a planetary mixer, etc. can be used. These apparatuses may also be used in appropriate combination.
[0040] As described above, the resin composition containing the inorganic oxide powder according to the present embodiment can simultaneously achieve a high dielectric constant and a low dielectric loss tangent. In addition, the resin composition containing the inorganic oxide powder according to the present embodiment has a low viscosity, so that it has good flowability and excellent moldability. EXAMPLES
[0041] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.
[0042] [Example 1] Titanium oxide powder 1 (manufactured by Toho Titanium Co., Ltd., product name: HT0110, average circularity 0.78, average particle size 5.9 μm) was spheroidized by a flame fusion method to obtain a spherical titanium oxide powder. The average circularity of the obtained spherical titanium oxide powder was 0.95. Next, an aluminum source (alumina fine powder (Nippon Aerosil Co., Ltd., product name: AEROXIDE (registered trademark) AluC)) was added to the spherical titanium oxide powder so that the aluminum content in the finally obtained inorganic oxide powder was 40 mass ppm. Thereafter, the raw material powder containing the alumina fine powder and the spherical titanium oxide powder was placed in an alumina crucible and heat-treated at an electric furnace temperature of 900 ° C. for 4 hours in an air atmosphere. After the heat treatment, the powder was naturally cooled until the inside of the furnace reached 200 ° C., and then the powder was collected and crushed in a mortar to obtain an inorganic oxide powder. The aluminum content, average circularity, average particle size, and specific surface area of the obtained inorganic oxide powder were measured by the following methods. The results are shown in Table 1.
[0043] <Method of measuring aluminum content> Measurements were performed in accordance with JIS R9301-3-4 and JIS 0116. 0.1 g of inorganic oxide powder was placed in a Teflon container, 2 mL of 6 M sulfuric acid was added, and the Teflon container was sealed and heated in a constant temperature dryer adjusted to 230°C for 16 hours. After cooling, the decomposition liquid was adjusted to 10 mL with pure water to prepare a test liquid. The test liquid was diluted with dilute sulfuric acid as necessary. The measurement sample was then analyzed by ICP emission spectroscopy (ICP spectrometer: Agilent, product name: 5110 VDV) to measure the aluminum content in the inorganic oxide powder. The measurement wavelength was 396.152 nm. The calibration curve was created using the following standard solutions. Titanium (purity 99.9% or more) was dissolved in 50 mL of 6 M hydrochloric acid by heating, and then the volume was adjusted to 100 mL to prepare a titanium solution. Aluminum standard solution (Al1000, Fujifilm Wako Pure Chemical Industries, Ltd.) was dispensed into 10 mL spinach tubes to give concentrations of 0 mg / L, 0.1 mg / L, 1.0 mg / L, and 10 mg / L, and 2 mL of 6 M sulfuric acid and 1 mL of titanium solution were added to the solution to prepare a standard solution for the calibration curve.
[0044] <Method for measuring average circularity> The inorganic oxide powder was fixed to a sample stage with carbon tape and then osmium-coated. Then, an image taken with a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-7001F SHL) at a magnification of 500 to 50,000 times and a resolution of 1280 x 1024 pixels was imported into a personal computer. This image was analyzed using an image analyzer (manufactured by Nippon Roper Co., Ltd., product name: Image-Pro Premier Ver.9.3) to calculate the projected area (S) and projected perimeter (L) of the particles constituting the powder, and then the circularity of the particles was calculated using the following formula (1). The circularity of 200 random particles was calculated, and the average value was taken as the average circularity of the inorganic oxide powder. Circularity = 4πS / L 2 (1)
[0045] <Method of measuring average particle size> The average particle size was measured using a laser diffraction particle size distribution analyzer (manufactured by Beckman Coulter, Inc., product name: LS 13 320). 3 100 g of pure water and 0.1 g of inorganic oxide powder were added and dispersed for 1 minute using an ultrasonic homogenizer (BRANSON, product name: SFX250). The dispersion of the inorganic oxide powder that had been dispersed was added drop by drop using a dropper to a laser diffraction particle size distribution measuring device, and measurements were taken 30 seconds after the specified amount was added. The particle size distribution was calculated from the data on the light intensity distribution of the diffracted / scattered light of the inorganic oxide powder detected by a sensor in the laser diffraction particle size distribution measuring device. The average particle size was calculated from the particle size corresponding to a cumulative value of 50% in the cumulative particle size distribution based on volume of the particle size to be measured.
[0046] <Method of measuring specific surface area> The measurement cell was filled with 1 g of inorganic oxide powder, and the specific surface area was measured using a Mountech Macsorb HM model-1201 fully automatic specific surface area diameter measurement device (BET one-point method). The degassing conditions before the measurement were 200°C and 10 minutes. Nitrogen was used as the adsorption gas.
[0047] The proportion of the rutile phase in the resulting inorganic oxide powder was measured by the following method. The results are shown in Table 1. <Method for identifying and measuring the content of crystalline phases in inorganic oxide powder> The measurement device used was a horizontal sample type multipurpose X-ray diffractometer (Rigaku Corporation, product name: RINT-UltimaIV), and the X-ray diffraction patterns of the inorganic oxide powders were measured under the following measurement conditions. X-ray source:CuKα Tube voltage: 40kV Tube current: 40mA Scan speed: 10.0° / min 2θ scan range: 10°~80° For quantitative analysis of the crystal phases, Rietveld method software (MDI, product name: Integrated Powder X-ray Software Jade+9.6) was used. The proportions (mass%) of various crystal phases were calculated by Rietveld analysis after X-ray diffraction measurement of a sample in which α-alumina (internal standard substance) (NIST), a standard sample for X-ray diffraction, was added to the inorganic oxide powder so that the content was 50 mass% (based on the total amount of the inorganic oxide powder sample after addition).
[0048] The obtained inorganic oxide powder was filled into a resin material, and the dielectric properties were evaluated by the following method. <Evaluation of dielectric properties (dielectric constant and dielectric tangent)> Inorganic oxide powder and polyethylene resin powder (manufactured by Sumitomo Seika Chemicals Co., Ltd., product name: FLOTHEN (registered trademark) UF-20S) were weighed so that the loading amount of inorganic oxide powder was 20 volume %, and mixed using a vibration mixer (manufactured by Resodyn) at an acceleration of 60 G and a processing time of 2 minutes to obtain a resin composition. The obtained resin composition was poured into a metal frame with a diameter of 3 cm in an amount to give a thickness of about 0.3 mm, and sheeted using a nanoimprint device (manufactured by SCIVAX, product name: X-300) under conditions of 140 ° C, 5 minutes, and 30,000 N. The obtained sheet was cut into a size of 1.5 cm x 1.5 cm to obtain an evaluation sample. Next, a 36 GHz cavity resonator (manufactured by Samtec Co., Ltd.) was connected to a vector network analyzer (manufactured by Keysight Technologies, product name: 85107), and the evaluation sample was placed so as to cover a 10 mm diameter hole provided in the cavity resonator, and the resonance frequency (f0) and unloaded Q value (Qu) were measured. The evaluation sample was rotated 60 degrees for each measurement, and the same measurement was repeated five times. The average values of the obtained f0 and Qu were taken as the measured values, and the dielectric constant was calculated from f0 and the dielectric loss tangent (tan δc) was calculated from Qu using analysis software (software manufactured by Samtec Co., Ltd.). The measurement was performed under conditions of a measurement temperature of 20°C and a humidity of 60% RH. The obtained values of dielectric constant and dielectric loss tangent were evaluated according to the following evaluation criteria. The results are shown in Table 1. (Evaluation Criteria) <Dielectric constant> 3 points: Dielectric constant is 4.8 or more 2 points: Dielectric constant is 4.5 or more and less than 4.8 1 point: Dielectric constant is 4.4 or more and less than 4.5 0 points: Dielectric constant less than 4.4 <Dielectric tangent> 3 points: Dielectric tangent is 4.6×10 -4 below 2 points: Dielectric tangent is 4.6×10 -4 Super, 5.1×10 -4 less than 1 point: Dielectric tangent is 5.1×10 -4 That's it, 5.6 x 10 -4 less than 0 points; dielectric tangent is 5.6×10 -4 End <Overall rating> The dielectric constant and dielectric tangent scores were totaled and the dielectric properties were evaluated according to the following criteria. Excellent: The dielectric constant and dielectric tangent scores are both 3 points (total score is 6 points). Good: Either the dielectric constant or the dielectric tangent is 3 points, and the other is 2 points (total score is 5 points). Pass: The dielectric constant and dielectric tangent both receive 2 points (total score is 4 points). Unacceptable: Either the dielectric constant or the dielectric tangent has a score of less than 2 (total score is 4 or less).
[0049] [Examples 2 to 7 and Comparative Examples 1 to 3] Inorganic oxide powders were prepared according to the compositions or manufacturing conditions shown in Table 1. Comparative Examples 2 and 3 are examples in which inorganic oxide powders were prepared without carrying out step (i). The inorganic oxide powders of each example were evaluated for aluminum content, average circularity, average particle size, specific surface area, proportion of rutile phase, and dielectric properties in the same manner as in Example 1. The results are shown in Table 1.
[0050] [Example 8] To 100 parts by mass of the inorganic oxide powder obtained in Example 1, 1 part by mass of hexamethyldisilazane (manufactured by Shin-Etsu Silicone Co., Ltd., product name: KBM-1003) was added as a surface treatment agent. Thereafter, the mixture was mixed for 2 minutes at an acceleration of 60 G using a vibration mixer (manufactured by Resodyn, product name: LabRAM II), and then dried for 24 hours in a mixed powder vacuum dryer under an environment of 120°C and less than -133 Pa to obtain a surface-treated inorganic oxide powder. The obtained inorganic oxide powder was evaluated for the aluminum content, average circularity, average particle size, specific surface area, proportion of rutile phase, and dielectric properties in the same manner as in Example 1. The results are shown in Table 1.
[0051] The raw materials used in the examples and comparative examples are as follows. <Raw titanium dioxide powder> Titanium oxide powder 1: manufactured by Toho Titanium Co., Ltd., product name: HT0110, average circularity 0.78, average particle diameter 5.9 μm. Titanium oxide powder 2: manufactured by Toho Titanium Co., Ltd., product name: HT0514, average circularity 0.72, average particle diameter 0.4 μm. <Aluminum source> Alumina: Alumina fine powder (Nippon Aerosil Co., Ltd., product name: AEROXIDE AluC, specific surface area: 100 m 2 / g).
[0052] [Table 1]
[0053] As shown in Table 1, the inorganic oxide powders of Examples 1 to 8, which satisfy the constitution of the present invention, were able to give resin compositions with high dielectric constants and low dielectric loss tangents. On the other hand, in Comparative Examples 1 to 3, which do not satisfy the constitution of the present invention, the resin compositions obtained were inferior in either the dielectric constant or the dielectric loss tangent. From the above results, it was confirmed that the inorganic oxide powder according to the present invention can simultaneously achieve a high dielectric constant and a low dielectric loss tangent when filled into a resin material. [Industrial Applicability]
[0054] The inorganic oxide powder according to the present embodiment can simultaneously achieve a high dielectric constant and a low dielectric tangent when filled into a resin material. Therefore, the inorganic oxide powder according to the present embodiment can be suitably used as a filler for a resin material. In addition, the resin composition containing the inorganic oxide powder according to the present embodiment has industrial applicability as a high-frequency substrate material, an insulating material, and the like.
Claims
1. An inorganic oxide powder comprising: The inorganic oxide powder includes a spherical titanium oxide powder and an aluminum oxide powder, The amount of aluminum in the inorganic oxide powder is 2500 to 50,000 ppm by mass, The inorganic oxide powder has a specific surface area of 5 m 2 / g or less.
2. 2. The inorganic oxide powder according to claim 1, wherein the inorganic oxide powder has an average circularity of 0.80 or more.
3. The inorganic oxide powder according to claim 1 or 2, wherein the average particle size of the inorganic oxide powder is 0.5 to 40 μm.
4. 3. The inorganic oxide powder according to claim 1, wherein the proportion of the spherical titanium oxide powder is 90 mass% or more based on the total mass of the inorganic oxide powder.
5. The inorganic oxide powder according to claim 1 or 2, which is surface-treated with a surface treatment agent.
6. The inorganic oxide powder according to claim 1 or 2, which is for filling a resin material.
7. The inorganic oxide powder according to claim 1 or 2, and at least one resin material selected from a thermoplastic resin and a thermosetting resin.
8. The method for producing an inorganic oxide powder according to claim 1 or 2, Spheroidizing titanium oxide powder by a powder fusion method; adding an aluminum source to the spheroidized titanium oxide powder; and heat-treating a raw material powder containing an aluminum source and a spherical titanium oxide powder.
Citation Information
Patent Citations
Preparation method of rutile titania nanospheres
CN107055606A
Rutile type titanium dioxide as well as preparation method and application thereof
CN112678867A
High purity titanium oxide and method for manufacturing the same
JP2003277057A
Near-infrared ray shielding agent and resin composition containing the same
JP2006126468A
Method for manufacturing spherical titanium oxide particle
JP2012246203A